A comparative study of ordered mesoporous carbons with different pore structures as anode materials for lithium-ion batteries1. Issue 53 (11th June 2015) - Saikia, Diganta; Wang, Tzu-Hua; Chou, Chieh-Ju; Fang, Jason; Tsai, Li-Duan; Kao, Hsien-Ming
<x xml:space="preserve">Abstract</x> Ordered mesoporous carbons CMK-3 and CMK-8 with different mesostructures are evaluated as anode materials for lithium-ion batteries. CMK-8 possesses higher reversible capacity, better cycling stability and rate capability than CMK-3.